2022
DOI: 10.1111/evo.14457
|View full text |Cite
|
Sign up to set email alerts
|

Termite nest evolution fostered social parasitism by termitophilous rove beetles

Abstract: Colonies of social insects contain large amounts of resources often exploited by specialized social parasites. Although some termite species host numerous parasitic arthropod species, called termitophiles, others host none. The reason for this large variability remains unknown. Here, we report that the evolution of termitophily in rove beetles is linked to termite nesting strategies. We compared one-piece nesters, whose entire colony life is completed within a single wood piece, to foraging species, which expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The latter is often the case in one-piece nesting termites (e.g., (Sugio et al, 2020)), whose colony life is completed within a piece of wood that serves as food and nest (Abe, 1987; Mizumoto and Bourguignon, 2020). Phylogenetic comparative analysis showed that one-piece nesting termites have smaller colony sizes than other nesting types (Mizumoto et al, 2022b), and thus, their total number of alates within a nest must be smaller. Because synchronization is not facilitated by social interactions when the number of alates is small (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The latter is often the case in one-piece nesting termites (e.g., (Sugio et al, 2020)), whose colony life is completed within a piece of wood that serves as food and nest (Abe, 1987; Mizumoto and Bourguignon, 2020). Phylogenetic comparative analysis showed that one-piece nesting termites have smaller colony sizes than other nesting types (Mizumoto et al, 2022b), and thus, their total number of alates within a nest must be smaller. Because synchronization is not facilitated by social interactions when the number of alates is small (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Species for which an estimate of mean colony size (mean number of individuals, excluding eggs) was available served as reference for the analysed sample, as this variable is the most difficult to measure. Colony size was obtained from published data compilations [34,[37][38][39][40] and references therein, complemented with several specific references not in the compilations [41][42][43][44][45][46][47]. Then, the remaining variables of interest were obtained from those same references if they provided such variables, or from other published data compilations on the respective subjects: sterile caste number [25], nest-food separation [48] and soilfeeding [21,49].…”
Section: Materials and Methods (A) Data Assemblymentioning
confidence: 99%
“…While some species are central‐place foragers, maintaining a nest and foraging distant resources, single‐piece nesting termites complete the entire life cycle of the colony within a single piece of dead wood. Thought to be the ancestral condition, around 19% of species are single‐piece nesting (Inward et al, 2007 ; Mizumoto et al, 2022 ). In these species, a high level of competition over the same nesting space and food resource results in frequent interactions between colonies that live at high densities (Thorne et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%